EPV 19. Dissociable regions for recognition and execution of conceptual and spatio-temporal action characteristics in acute stroke patients. Issue 9 (September 2016) - Martin, M.; Dressing, A.; Beume, L.; Bormann, T.; Mader, I.; Rijntjes, M.; Kaller, C.P.; Weiller, C.
Abstract : The ability to recognize and respond to actions performed by others is fundamental for a wide range of activities involving social interactions. However, despite an enormous number of functional imaging studies, a precise delineation of the brain regions crucial for distinct aspects of action recognition has remained elusive. Moreover, the degree of overlap between regions involved in active action performance is controversial. To elucidate these issues, 98 acute stroke patients (68 male, age mean  ±  SD, 65  ±  13 years) were examined in the acute period after stroke (mean  ±  SD 4.4  ±  2 days after symptom onset). First, action recognition was assessed with a newly designed test which required patients to distinguish between correctly and incorrectly performed tool-associated actions depicted in short videos. Errors categories comprised conceptual (e.g., spreading jam on toast with a paint brush), and spatio-temporal errors (orientation of the tool, hand configuration, and movement kinematics). Second, actual use of tools was probed using an established test which, in analogy to the error categories for action recognition, included separate measures for the ability to match tools and recipients (e.g., hammer – nail; conceptual score), and for the quality of the executed action (e.g., hammering; spatio-temporal score). Lesions were delineated on diffusion-weighted scans for voxel-based lesion-symptom mapping. Impaired recognition of conceptual errors was associated mainly with lesions to the anterior middle temporal gyrus as well as to the caudal middle frontal gyrus. Conversely, the detection of spatio-temporal errors depended on the posterior superior temporal gyrus and sulcus, inferior parietal lobule (IPL) and ventral premotor cortex (vPMC). Analyses for distinct spatio-temporal error subcategories revealed that superior temporal lesions specifically affected the recognition of kinematic and tool orientation errors, while inferior parietal and premotor damage selectively impaired the discrimination of hand configurations. Lastly, compared to the recognition of conceptual and spatio-temporal errors, both active tool-recipient matching and action execution, respectively, were more dependent on the IPL and vPMC; conversely, action recognition deficits were more strongly associated with occipito-temporal and superior temporal lesions. The results demonstrate that action recognition is enabled by a network of dissociable regions that are specialized for the processing of distinct action features. While the decoding of conceptual action aspects relies mainly on anterior temporal regions, IPL and vPMC mediate the recognition of hand configurations, and the posterior superior temporal lobe is crucial for the processing of movement kinematics and tool orientation. Our findings show that, with the exception of the hand configuration, action recognition does not rely on the fronto-parietal regions that subserve the performance of actual tool use.